2019
DOI: 10.1038/s41467-019-09442-0
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of Loa loa

Abstract: Elimination of the helminth disease, river blindness, remains challenging due to ivermectin treatment-associated adverse reactions in loiasis co-infected patients. Here, we address a deficit in preclinical research tools for filarial translational research by developing Loa loa mouse infection models. We demonstrate that adult Loa loa worms in subcutaneous tissues, circulating microfilariae (mf) and presence of filarial biomarkers in sera occur following experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 45 publications
(68 reference statements)
5
56
0
Order By: Relevance
“…In addition, their spectra can be easily adjusted and are diverse. 27,28 This series of BMN-Fluors, which are in constant rotation in a free state, can sequentially self-regulate their conformations to form different stable conformations when they encounter the AP site. BMN-Fluors can emit different types of signals, including an "OFF-ON" single-channel signal, a "ratio" double-channel signal, and even a precise multichannel signal.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their spectra can be easily adjusted and are diverse. 27,28 This series of BMN-Fluors, which are in constant rotation in a free state, can sequentially self-regulate their conformations to form different stable conformations when they encounter the AP site. BMN-Fluors can emit different types of signals, including an "OFF-ON" single-channel signal, a "ratio" double-channel signal, and even a precise multichannel signal.…”
Section: Introductionmentioning
confidence: 99%
“…A major reason for the limited understanding of loiasis-associated immune responses and clinical picture [29,30] is the lack of appropriate infection models. Besides the established rodent models of Brugia malayi and Onchocerca volvulus [23,[31][32][33], we recently showed that BALB/c with impaired IL-4, IL-5 and IL-13 signalling as well as a lymphopenic γc-deficient strain allow development of L. loa life stages [22,34]. This was also reflected in our studies with the rodent Litomosoides sigmodontis model since in IL-4Rα/IL-5 −/− BALB/c mice, worm burden and MF counts were significantly higher than in wildtype BALB/c control groups [35], suggesting that principally mice lacking Th2 responses provide a better environment for worm growth.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, groups of female and male wildtype BALB/c mice were exposed to either: (i) a s.c. injection of 500 L3 in 100 µl RPMI-1640 medium isolated from Chrysops flies; (ii) 10,000 MF via the tail vein in 100 µl RPMI-1640 medium isolated from human peripheral blood [22], or (iii) 10 L4; (iv) 10 L5; and (v) 10 adult worms all isolated from infected-BALB/cRAG2γc −/− mice. Whereas L4 were injected s.c. in 100 µl of RPMI-medium, L5 and adult stages were implanted as previously described [23].…”
Section: Pre-clinical Experimental Studies With Different Loa Loa Lifmentioning
confidence: 99%
“…Intrathoracic injections of flies with mf bypass feeding of flies on donors, and therefore address the ethical concerns of human landing catch. The use of animal sources of mf, such as splenectomised baboons [11] or immunodeficient mice [18] would potentially completely obviate the use of human donors and may achieve a complete laboratory life cycle local to a source of wild-caught vectors. Further, high yielding production of L3 following experimental infections of Chrysops would be a significant improvement in throughput for translational medicine applications compared to standard methods.…”
Section: Introductionmentioning
confidence: 99%
“…Further, high yielding production of L3 following experimental infections of Chrysops would be a significant improvement in throughput for translational medicine applications compared to standard methods. In this study, we assessed if intrathoracic L. loa mf injected C. silacea can survive under laboratory conditions for a minimum of two weeks and whether L3 infective larvae recovered from lab maintained flies could maintain their viability and development both in vitro and in vivo taking advantage of recent advances in L. loa culture systems and mouse models developed by our laboratories [12,18].…”
Section: Introductionmentioning
confidence: 99%